Gall stone abscess, a delayed complication following laparoscopic cholecystectomy - Aruni, Amaresh; Kumar, Hemanth; Singh, Harjeet; Nagaraj, Satish Subbiah (International Surgery Journal, 2019)
In the current era of minimally invasive surgeries, laparoscopic cholecystectomy being the popular surgery for the symptomatic cholelithiasis and complications pertaining to these minimally invasive surgeries, here we report a complication related to gall stone spillage after 4 months of surgery in 80-year male patient presenting as abdomen lump. The risk of stone spillage and complications related to it are more than open cholecystectomy. Careful dissection, extraction and complete retrieval of all the spilled stones can avoid these complications and hence complication related to stone spillage can be potentially avoided, and intra-operative documentation of the gall stone spillage can help to think for early diagnosis and treatment of the complications.